Raised Erythrocyte Sedimentation Rate in Asymptomatic Hyperlipidaemia. Issue 5868 (23rd June 1973) - Böttiger, L. E.; Carlson, L. A.; Ekelund, L.-G.; Olsson, A. G.
Abstract : In 101 subjectively healthy persons, who at a routine health examination were found to be markedly hyperlipidaemic, the erythrocyte sedimentation rate (E.S.R.) was significantly raised. The E.S.R. was raised above 25 mm/hr in 44, 64, and 23% respectively of subjects with type II A, II B, and IV hyperlipoproteinaemia in comparison to only 6% in sex- and age-matched normolipidaemic controls. Several explanations for this E.S.R. elevation have been studied. The levels of plasma lipoproteins do not appear themselves to influence the E.S.R., as among other things there was no difference in plasma concentrations of cholesterol and triglycerides in hyperlipidaemic persons with high and low E.S.R. The concentration of lysolecithin, which may decrease the E.S.R. was the same in the hyperlipidaemic persons with high E.S.R. as in those with low. However, the incidence of ischaemic exercise E.C.G. changes was 38% in the hyperlipidaemic subjects with E.S.R. below 24 mm/hr and 72% in those with E.S.R. above 25 mm/hr. For the time being one possible reason for the raised E.S.R. thus seems to be that the hyperlipidaemia causes silent vascular disease that in its turn produces the E.S.R. elevations.